Hydride Pinning Pathway in the Hydrogenation of CO2 to Formic Acid on Dimeric Tin Dioxide. Issue 5 (12th February 2019) - Sarma, Plaban Jyoti; Baruah, Satyajit Dey; Logsdail, Andrew; Deka, Ramesh Chandra
Abstract: Capture of CO2 and its conversion into organic feedstocks are increasingly needed as society moves towards a renewable energy economy. Here, a hydride‐assisted selective reduction pathway is proposed for the conversion of CO2 to formic acid (FA) over SnO2 monomers and dimers. Our density functional theory calculations infer a strong chemisorption of CO2 on SnO2 clusters forming a carbonate structure, whereas heterolytic cleavage of H2 provides a new pathway for the selective reduction of CO2 to formic acid at low overpotential. Among the two investigated pathways for reduction of CO2 to HCOOH, the hydride pinning pathway is found promising with a unique selectivity for HCOOH. The negatively‐charged hydride forms on the cluster during the dissociation of H2 and facilitates the formation of a formate intermediate, which determines the selectivity for FA over the alternative CO and H2 evolution reaction. It is confirmed that SnO2 clusters exhibit a different catalytic behaviour from their surface equivalents, thus offering promise for future work investigating the reduction of CO2 to FA via a hydride pinning pathway at low overpotential and CO2 capturing. Abstract : Different ways : The modelled Sn2 O4 cluster has shown a unique selectivity towards HCOOH when the mechanism proceeds via hydride assisted pathway (commiting step) over CO formation and H2 recombination reactions (limiting steps).